Apelin-13 Pretreatment Promotes the Cardioprotective Effect of Mesenchymal Stem Cells against Myocardial Infarction by Improving Their Survival - Guona Chen; Xiaoting Liang; Qian Han; Cong Mai; Linli Shi; Zhuang Shao; Yimei Hong; Fang Lin; Mimi Li; Bei Hu; Xin Li; Yuelin Zhang (Stem Cells International)
Although mesenchymal stem cell- (MSC-) based therapy has shown promising results for myocardial infarction (MI), low cell survival heavily limits its beneficial effects. Apelin plays an essential regulatory role in cell proliferation. This study was aimed at determining whether Apelin-13 pretreatment could improve the survival of MSCs in the ischemic heart and enhance their cardioprotective efficacy against MI. MSCs were pretreated with or without Apelin-13 for 24 hours and then exposed to serum deprivation and hypoxia (SD/H) for 48 hours. The mitochondrial morphology of MSCs was assessed by MitoTracker staining. The apoptosis of MSCs was determined by TUNEL staining. The level of mitochondrial reactive oxygen species (ROS) of MSCs was detected by Mito-Sox staining. MSCs and Apelin-13-pretreated MSCs were transplanted into the peri-infarct region in a mouse MI model. Apelin-13 pretreatment protected MSCs against SD/H-induced mitochondrial fragmentation and apoptosis. Apelin-13 pretreatment reduced ROS generation induced by SD/H in MSCs. Furthermore, Apelin-13 pretreatment enhanced the angiogenesis of MSCs under SD/H conditions. Mechanistically, Apelin-13 pretreatment inhibited SD/H-induced MSC apoptosis by downregulating mitochondrial fission via activation of the ERK pathway, and these effects were partially abrogated by ERK inhibitor U0126. Apelin-13 pretreatment promoted the survival of MSCs in the ischemic heart. Moreover, transplantation with Apelin-13-pretreated MSCs improved heart function and increased angiogenesis accompanied by decreased fibrosis compared with MSC transplantation at 28 days following MI. These findings reveal that pretreatment with Apelin-13 improves MSCs survival and enhances their therapeutic efficacy for MI. Our study provides a novel approach to improve MSC-based therapy for cardiovascular disease.